ERROR ANALYSIS ON ENGLISH PURE VOWELS PRONUNCIATION PRODUCED BY CUSTOMER SERVICE CENTER OFFICERS IN JUANDA AIRPORT - MUTIARA, RISKI ISNI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Key words: error, error analysis, English pure vowels.This study was aimed to investigate the errors in pronouncing English pure vowels which were produced by the Customer Service Center officers in Juanda Airport and the possible factors which caused them. In this study, the pure vowels examined were /iː/, /ɪ/, /ʊ/, /uː/, /e/, /ǝ/, /ɜ:/, /ɔː/, /æ/, /ʌ/, /ɑ:/, and /ɒ/.In this study, the researcher used qualitative approach because she focused on the explanation and description rather than specific number. The data of this study was the recording of English pure vowels pronunciation produced by 13 Customer Service Center officers in Juanda Airport. In getting the data, the writer used two instruments. Those were the pronunciation test which was formulated based on the theory from Kelly (2011) about English pure vowels and the questionnaire which was formulated based on the theory from Murcia et.al (2010) about factors affecting the learning of pronunciation. In analyzing the data, the researcher did the process of error identification, error description and explanation.The finding revealed that most of the errors were in form of substitution and some were in form of addition. There were 11 vowels regarded as the most problematic to pronounce, those were vowels /i:/ , /ʊ/ /u:/, /ə/,  /ɜ:/ , /ↄ:/, /æ/, /ɑ:/, /ɒ/, /ə/, /Ʌ/, and /ɪ/. In addition, there were three possible factors causing the errors in pronouncing English pure vowels. Those factors were the role of native language,the unfamiliarity toward English words, and the lack exposure of English uses. However, the role of native language, especially about the different phonemic system between the native language and the target language and the unfamiliarity toward English words made the officers pronounced the words which were tested as they assumed.By this study, the researcher would like to suggest that further researchers conduct similar studies with the different subject like error analysis on Indonesian pure vowels which are produced by Indonesian learners who come from English speaking country.